The 2nd China Bioanalysis Forum Annual Conference: clinical bioanalysis and large molecule bioanalysis. (October 2014) - Tang, Daniel; Zhong, Dafang; Dong, Kelly
Beijing, China, 7–8 June 2014. The second China Bioanalysis Forum (CBF) conference was successfully held in Beijing, China, in June 2014 and covered the theme of clinical bioanalysis and large molecule bioanalysis. Compared with the first conference in 2013, this conference was attended by scientists from a greater number of scientific disciplines and geographic areas. This report summarizes the major topics in the conference as well as the future plan of the CBF.